Cover Feature: Structurally Constrained MUC1‐Tn Mimetic Antigen as Template for Molecularly Imprinted Polymers (MIPs): A Promising Tool for Cancer Diagnostics (ChemPlusChem 9/2022). Issue 9 (7th July 2022) - Palladino, Pasquale; Papi, Francesco; Minunni, Maria; Nativi, Cristina; Scarano, Simona
Abstract : The cover feature image shows the possibility to replace the use of monoclonal antibodies with an innovative class of catecholamine‐based Molecularly Imprinted Polymers (MIPs). MIPs are synthetic receptors characterized by high sensitivity and specificity towards the imprinted target. Here, the imprinted targets are the native TnThr mucin antigen, over‐expressed in several adenocarcinomas including the very aggressive Triple Negative Breast Cancer (TNBC), and the structurally locked TnThr mimetic. Cover design by Francesco Papi. More information can be found in the Research Article by C. Nativi, S. Scarano, and co‐workers .